Posted by cassie on Friday, February 10, 2012 at 1:22am.
Let f(x) be the function 1/x+5. Then the quotient
f(6+h)−f(6)/h can be simplified to −1/ah+b for:
a= 11
b=
I did all the work to get a but for some reason the number that I keep getting for "B" is wrong

calculus  hasan, Friday, February 10, 2012 at 2:14am
prove d/dx (csc x) = −csc x cot x

calculus  Reiny, Friday, February 10, 2012 at 8:30am
First of all , I think you meant f(x) = 1/(x+5)
the difference quotient is
(f(l+h)  f(6))/h
= (1/(11+h)  1/11 )/h
= (11  11  h)/(11(11+h) (1/h)
= 1 / (11(11+h))
I notice another error is your typing
you probably meant to type:
..... can be simplified to 1/(a(h+b) )
compare 1/(11(11+h)) to 1/(a(h+b))
since we are told a=11, clearly b has to be 11 for them to match